2023
DOI: 10.1039/d3cc01542d
|View full text |Cite
|
Sign up to set email alerts
|

Disproportionation of Sn(ii){CH(SiMe3)2}2 to ˙Sn(iii){CH(SiMe3)2}3 and ˙Sn(i){CH(SiMe3)2}: characterization of the Sn(i) product

Abstract: Half a century since the photocatalytic disproportionation of Lappert's dialkyl stannylene SnR2, R = CH(SiMe3)2 (1) gave the persistent trivalent radical [·SnR3], the characterization of the corresponding Sn(I) product, ·SnR...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…2.0–2.5 eV) 8,9 and often well-defined Sn( i ) radical character. 10,11 It has been shown that stannylenes react with H 2 , 9,12,13 CO 2 , 14–16 RNH 2 , 9 and ROH (R = Me or H) 17 and ethylene 6 under mild conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2.0–2.5 eV) 8,9 and often well-defined Sn( i ) radical character. 10,11 It has been shown that stannylenes react with H 2 , 9,12,13 CO 2 , 14–16 RNH 2 , 9 and ROH (R = Me or H) 17 and ethylene 6 under mild conditions.…”
mentioning
confidence: 99%
“…6,23,30 Homolytic cleavage of a Sn–C bond was initiated upon heating, followed by the formation of a :ṠnAr iPr4 radical and a terphenyl carbon radical ˙Ar iPr4 , which can be contrasted with the generation of the radical ˙Sn{CH(SiMe 3 ) 2 } 3 by heating hydrocarbon solutions of {Sn{CH(SiMe 3 ) 2 } 2 } 2 . 10,11,39 The reaction of the :ṠnAr iPr4 /˙Ar iPr4 radical pair with phenylacetylene yielded the product 1 . In the synthesis of 2 , the ˙Ar iPr4 is not added to the alkyne substrate, likely for steric reasons.…”
mentioning
confidence: 99%